2018
DOI: 10.1177/1758835918780312
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of breast cancer brain metastases: challenges, emerging treatments and perspectives

Abstract: Brain metastases are the most common central nervous system tumors in adults, and incidence of brain metastases is increasing due to both improved diagnostic techniques (e.g. magnetic resonance imaging) and increased cancer patient survival through advanced systemic treatments. Outcomes of patients remain disappointing and treatment options are limited, usually involving multimodality approaches. Brain metastases represent an unmet medical need in solid tumor care, especially in breast cancer, where brain meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 80 publications
(108 reference statements)
1
41
0
2
Order By: Relevance
“…Moreover, the BBB and the crosstalk between malignant and brain cells favor brain metastasis (Wilhelm et al , ). Altogether, this renders the brain a sanctuary against antitumor strategies, hindering the treatment of brain metastases with the available current therapies (Kotecki et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the BBB and the crosstalk between malignant and brain cells favor brain metastasis (Wilhelm et al , ). Altogether, this renders the brain a sanctuary against antitumor strategies, hindering the treatment of brain metastases with the available current therapies (Kotecki et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…With better control of systemic disease, many women who have stable primary disease, or respond to initial treatment, ultimately develop BCBM. Thus, while survival of primary breast cancer is improving, the incidence of BCBM is increasing 2 .…”
mentioning
confidence: 99%
“…In contrast, there are limited targeted therapies available with modest therapeutic responses to target distant metastasis in ERBB2 + BC patients [ 3 , 44 , 45 ]. The optimization of targeted therapies against metastatic ERBB2 + BC is challenging for several reasons, including molecular and metabolic adaptations in metastasizing cells, refractive organ-specific microenvironments, and lack of preclinical models to evaluate therapeutic targets [ 9 , 46 , 47 , 48 ]. In this study, we reported an orthotopic model of spontaneous ERBB2 + BC BrM that can be used to evaluate therapeutic approaches targeting both the primary tumor and distant metastases together, suggesting its high clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The poor therapeutic response towards targeted therapies in metastatic ERBB2 + BC is attributed in part to clonal evolution in metastatic cells, their adaptation to the organ-specific microenvironment, and differential drug delivery to the metastatic niche [ 4 , 5 , 6 ]. This is exemplified by the presence of the blood–brain barrier (BBB) in the case of BrM, which has one of the poorest outcomes among all metastatic BCs [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%